Recent speciation associated with range expansion and a shift to self-fertilization in North American Arabidopsis - Willi, Yvonne; Lucek, Kay; Bachmann, Olivier; Walden, Nora (Nature Communications, 2022)
The main processes classically evoked for promoting reproductive isolation and speciation are geographic separation reducing gene flow among populations, divergent selection, and chance genomic change. In a case study, we present evidence that the additional factors of climate change, range expansion and a shift in mating towards inbreeding can initiate the processes leading to parapatric speciation. At the end of the last Pleistocene glaciation cycle, the North American plant Arabidopsis lyrata expanded its range and concomitantly lost its reproductive mode of outcrossing multiple times. We show that in one of the newly colonized areas, the self-fertilizing recolonization lineage of A. lyrata gave rise to selfing A. arenicola, which expanded its range to subarctic and arctic Canada and Greenland, while the parental species remained restricted to temperate North America. Despite the vast range expansion by the new species, mutational load did not increase, probably because of selfing and quasi-clonal selection. We conclude that such peripheral parapatric speciation combined with range expansion and inbreeding may be an important but so far overlooked mode of speciation.